MULTI-AKAD DALAM PERSPEKTIF FIKIH DAN IMPLEMENTASINYA DI PERBANKAN SYARIAH - Alfin, Aidil (Alhurriyah, 2015)
Social changes have significant influence to the various sides of life, including financial transactions. Construction contract which previously only known one contract for one transaction (al-'uqud al-Basithah), now has grown to such an extent that in almost all the Shari'ah banking covenants built more than one contract for one-time transactions, for example Musharaka Mutanaqishah (merger between shirkah owned by Ijarah contract), Ijarah Muntahiy Bittamlik (merger between Ijarah contract and purchase) and Murabaha lil bi amir al-syira '(merging two sale and purchase agreement). In principle, the same legal origin of the hybrid contract with a single contract, it could be legitimate and can also be imperfect. Prohibition hybrid contract as the hadith of Abu Hurayrah is not absolute. During the merger agreement-contract does not contain ghahar / jahalah and does not lead to usury, the hybrid contract valid from the perspective of Islamic jurisprudence.